The Effect of Servicescape on Consumer Loyalty Through Consumer Satisfaction as a Variable Intervening at the Coffee Crowd Medan - Syahputra, Aditia; Sanny, Annisa; Ritonga, Husni Muharram (Universitas Negeri Medan, 2022)
This study intends to examine the relationship between the servicescape and client loyalty, with customer happiness serving as an intermediate measure. The investigation was conducted at the The Coffee Crowd location in Sun Plaza. This is an example of causal association research. In this study, 95 responses represented the sample size. Using the SmartPLS software, PLS-SEM was utilized to perform data analysis. The outcomes demonstrated that servicescape has a favorable and statistically significant impact on customer satisfaction. Customer loyalty is positively and significantly affected by servicescape and customer happiness. servicescape has a favorable and considerable effect on customer satisfaction and consumer loyalty.